Improve Organizational Performance by Implementing the Dimensions of Total Quality Management With Respect to the Mediating Role of Organizational Innovation Capability - Bazrkar, Ardeshir; Aramoon, Erfan; Hajimohammadi, Mohammad; Aramoon , Vahid (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2022)
The results of the research show that the implementation of total quality management can improve processes and public participation in doing the best work in the organization, which in turn can increase market share, increase profits, increase product sales, reduce Waste and rework have a positive effect. The purpose of this study was to investigate the effect of total quality management on organizational performance with respect to the mediating role of organizational innovation capability in Iran Khodro Company. The present study was applied based on the purpose and survey-correlational in terms of data collection. Accordingly, after studying the theoretical foundations and research background in the field of total quality management, organizational performance and organizational innovation capability, effective dimensions were identified and introduced in the form of a conceptual model. The statistical sample of this research consisted of 222 middle managers of Iran Khodro Company’s headquarters. A researcher-made questionnaire was used to collect research data, the validity and reliability of which were confirmed. In order to fit the conceptual model of the research and test the research hypotheses, the structural equation modeling method was used in Smart PLS software. The results of testing research hypotheses showed that the dimensions of total quality management (hard quality management and soft quality management) have a positive and significant effect on organizational performance and organizational innovation capability. Organizational, the organizational innovation capability variable has an influential mediating role.